Money and Credit in the Fifteenth Century: Some Lessons from Yorkshire - Kermode, Jennifer I. (Business History Review, 1991)
This article explores some of the methods used to raise credit in an important trading region of late medieval England during a decline in overseas trade and an international bullion famine. It argues that, because provincial credit arrangements depended on local as well as national factors, a combination of demographic and regional circumstances contributed to the commercial weakness of Yorkshire merchants as they faced growing competition from Londoners with access to more sophisticated financial networks.
Keywords: Business History and gender